“ҲИБАТУЛ-ҲАҚОЙИҚ”ДАГИ АЙРИМ ЎЗЛАШМАЛАР ХУСУСИДА - sindorov, lutfulla (FILOLOGIYA UFQLARI JURNALI, 2021)
In thisarticle semes and etimology of some derived words used in “Hibatul haqoyiq” by Ahmad Yugnakiy are expounded. Lexical items on the derived layer of words in “Hibatul haqoyiq” are comparatively analysed with old Turki language and the words of Karakhaniy period as well XIV century sources.